Prácticas de ciencia abierta vistas desde la perspectiva de las comunidades de investigadores de las ciencias básicas de Perú - Manco, Alejandra (Revista Científica, 2023)
This article explores researchers' different open science practices in the process for generating knowledge in basic sciences (biology, chemistry, and physics), using a qualitative approach with eight semi-directed interviews. The main perceived effect of open science is the access to research inputs, i.e., open access to articles, open research data – especially the reuse of data and paradata –, and the reuse of codes as main sources. Another topic is the increased and accelerated collaboration with other colleagues, as well as the promotion of the exchange of ideas, i.e., it is a cultural change caused by the exchange of information. However, this work also explores the fact that the implementation of open science policies has unintended consequences, such as the creation of new inequalities or the reproduction of those that already exist in science. Finally, the issue of scientific communication as part of the conceptualization of open science is also mentioned by different researchers, although it is a subject that remains to be explored.